A superposition method to evaluate the strength of propellers in crushed ice flow considering collision and hydrodynamic load - Wu, Haiyan; Liu, Jingjing; Yu, Long; Wang, Youjiang (Norwegian University of Science and Technology, Department of Marine Technology, 2024)
Polar ships play a crucial role in the exploitation of Arctic resources, and their propellers are threatened by ice loads. Therefore, it is vital to investigate ice loads and conduct strength checks on propellers. In this study, a superposition method to evaluate the strength of propeller in crushed ice flow is established and numerical simulation methods is used to conduct research. Firstly, according to URI3, the potentially hazardous areas where crushed ice-propeller collision may occur could be determined, and the flow characteristics considering crushed ice-propeller interaction is calculated based on computational fluid dynamics (CFD)-discrete element method (DEM), and loads on blade surfaces can be extracted as input conditions in the next step. The ice in flow is unbreakable. Then, the strength analysis is completed with Finite Element Method (FEM), where pressure loads are derived from flow field calculations. The results indicate that ice particles from the front of the propeller are prone to collide with the pressure surface near the leading edge. The hydrodynamic performance of the propeller is also affected, with a decrease in propulsive efficiency in ice flow and a greater reduction with increasing advance coefficient.